Glass spinning cell at DuPont Experimental Station (1937)
General view of a glass spinning cell used during the early stages of nylon production and research at the DuPont Experimental Station in Wilmington, Delaware. In this design, the nylon polymer was melted in the glass chamber visible at the center of the photograph, which allowed researchers to study bubbles in the melt resulting from the decomposition of the polymer. Per this process, nylon chips were fed into the funnel situated at the top of the apparatus and dropped into a lock-chamber, where the air was exhausted and replaced with pure nitrogen. The chips were then dropped onto a heated grid and passed through a gear pump, filter, and spinneret before the resulting fiber was finally wound onto the bobbin visible on the lower left-hand side.
Keywords: Nylon; Scientific apparatus and instruments; Polymers; Nylon--Testing; E.I. du Pont de Nemours & Company. Experimental Station; E.I. du Pont de Nemours & Company; Machinery